miRNA-Coordinated Schizophrenia Risk Network Cross-Talk With Cardiovascular Repair and Opposed Gliomagenesis - Cao, Hongbao; Baranova, Ancha; Yue, Weihua; Yu, Hao; Zhu, Zufu; Zhang, Fuquan; Liu, Dongbai (Frontiers in Genetics, 2020)
Background Schizophrenia risk genes are widely investigated, while systemic analysis of miRNA contributing to schizophrenia is lacking. Methods Schizophrenia-associated genetic loci profile was derived from genome-wide association study (GWAS) of Schizophrenia Working Group of the Psychiatric Genomics Consortium (PGC) dataset. Experimentally confirmed relationships between miRNAs and their target genes were retrieved from miRTarBase. Competitive gene set association analysis for miRNA-target regulations was conducted by the multi-marker analysis of genoMic annotation (MAGMA) and further validated by literature-based functional pathway analysis using Pathway Studio. The associations of the targets of three miRNAs with schizophrenia were further validated using a GWAS of antipsychotic treatment response. Results Three novel schizophrenia-risk miRNA, namely, miR-208b-3p, miR-208a-3p, and miR-494-5p and their targetomes converge on two calcium voltage-gated channel subunit alpha1 C (CACNA1C) and B-cell lymphoma 2 (Bcl-2), well-known as contributors to schizophrenia. Both miR-208a-3p and miR-208b-3p reduce expression of the RNA-binding protein Quaking (QKI), whose suppression commonly contributes to demyelinating model of schizophrenia and to ischemia/reperfusion injury. Both QKI and hsa-miR-494-5p simultaneously contribute to the risk of schizophrenia and serve as the inhibitors of gliomagenesis. Conclusion Presented results point at an orchestrating role of miRNAs in pathophysiology of schizophrenia. Cellular effects of risk-associated miRNAs align with the primary etiological hypotheses of schizophrenia. The sharing of regulatory networks schizophrenia and other pathologies may explain higher cardiovascular mortality and lower odds of gliomagenesis previously reported in psychiatric patients.